A wear-resistant carbon fiber synchronous belt and preparation method thereof

By using synchronous belt film made of chlorosulfonated polyethylene and other materials on the carbon fiber synchronous belt, combined with corona discharge and vulcanization treatment, the problem of insufficient wear resistance of carbon fiber synchronous belt is solved, and high-strength and heat-resistant aging are achieved It has significant improvement in performance and cold resistance, suitable for large-scale production.

CN118852803BActive Publication Date: 2024-12-13NINGBO FULONG SYNCHRONOUS BELT
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411336459.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-13
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

During the use of existing carbon fiber synchronous belts, there are problems such as insufficient wear resistance, mechanical and mechanical properties, heat-aging resistance and cold resistance to improve.

Method used

Synchronous tape film made of chlorosulfonated polyethylene, epoxidized natural rubber, methylvinyl phenyl silicone rubber, cellulose nanocrystals, inorganic fillers, specific coupling agents and vulcanizing agents, and other materials, and is covered with Carbon fiber synchronous belt on the frame and is treated with corona discharge and vulcanization to improve the strength and wear resistance of the material.

Benefits of technology

It significantly improves the strength, wear resistance, heat aging resistance and cold resistance of the synchronization belt, extends the service life of the product, and simplifies the process flow, suitable for continuous large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

A wear-resistant carbon fiber synchronous belt and a preparation method thereof, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials: chlorosulfonated polyethylene, epoxidized natural rubber, methyl vinyl phenyl silicone rubber, cellulose nanocrystals, inorganic fillers, 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,4,6-trivinylcycloboroxine, 2,6-diamino-9H-fluorene-9-one, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, coupling agent, vulcanizing agent, antioxidant, anti-scorch agent and lubricant. The synchronous belt has high strength, good wear resistance, excellent heat aging resistance and cold resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synchronous belt transmission, and in particular to a wear-resistant carbon fiber synchronous belt and a preparation method thereof. Background Art

[0002] The transmission belt is an indispensable standard part in mechanical transmission devices. It combines the advantages of belt drive, chain drive and gear drive. When rotating, power is transmitted by meshing the belt teeth with the tooth grooves of the wheel. Therefore, there will be no asynchronous transmission between the belt and the pulley due to slip during the transmission process. It has the advantages of accurate transmission ratio, high transmission efficiency, large transmission power range, high transmission compliance, smooth transmission, small impact, no lubrication, no pollution, low noise, etc. It is widely used in various types of mechanical transmission in various industries such as machine tools, textiles, light industry, tobacco, petroleum, communication cables, chemicals, mining, metallurgy, automobiles, food, instruments and equipment.

[0003] At present, the synchronous belts used in various industries are prone to deformation during use, have poor creep resistance, poor dimensional precision, and need to be further improved in terms of heat resistance, wear resistance and aging resistance, as well as short service life. One of the effective ways to solve the above problems is to use carbon fiber twisted ropes to form the reinforcement skeleton of the synchronous belt to make a carbon fiber synchronous belt. However, the existing carbon fiber synchronous belts still have more or less technical defects such as insufficient wear resistance, and the mechanical properties, heat aging resistance and cold resistance need to be further improved.

[0004] In order to solve the above problems of the existing carbon fiber synchronous belt, the Chinese invention patent with the authorization announcement number CN115679711B discloses a multifunctional carbon fiber reinforced polyurethane rubber synchronous toothed belt and a preparation method. The synchronous toothed belt comprises a back belt surface rubber functional layer, a polyurethane rubber base belt layer, a carbon fiber skeleton layer, belt teeth and tooth surface arranged in sequence; the back belt surface rubber functional layer is any one of polyurethane rubber, natural rubber, nitrile rubber, EPDM rubber and silicone rubber. The carbon fiber skeleton layer accounts for 5-25% of the thickness of the back belt surface rubber layer; the carbon fiber skeleton layer is a carbon fiber fabric woven from different tow carbon fibers; the carbon fiber fabric is subjected to surface treatment and sizing treatment in sequence; the sizing rate of the carbon fiber fabric is 0.5-0.8%, the surface tension of the sizing agent is 43-47mN / m, and the viscosity is 1.5-2.5cp. The synchronous toothed belt prepared by the invention has high strength, good wear resistance, low elongation and good dimensional stability. However, its aging resistance and cold resistance still need to be further improved.

[0005] It can be seen that it is particularly important to develop a wear-resistant carbon fiber synchronous belt with high strength, good wear resistance, excellent heat aging resistance and cold resistance and a preparation method thereof. Summary of the invention

[0006] The main purpose of the present invention is to provide a wear-resistant carbon fiber synchronous belt with high strength, good wear resistance, excellent heat aging resistance and cold resistance and a preparation method thereof.

[0007] To achieve the above purpose, the present invention provides a wear-resistant carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 35-45 parts of chlorosulfonated polyethylene, 15-20 parts of epoxidized natural rubber, 25-35 parts of methyl vinyl phenyl silicone rubber, 5-8 parts of cellulose nanocrystals, 10-20 parts of inorganic fillers, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H) -triketone 1-3 parts, 2,4,6-trivinyl cycloboroxane 2-4 parts, 2,6-diamino-9H-fluorene-9-one 3-5 parts, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane 2-4 parts, 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 0.8-1.3 parts, coupling agent 2-4 parts, vulcanizing agent 3-5 parts, antioxidant 1-3 parts, anti-scorch agent 0.4-0.6 parts, lubricant 1-3 parts; the synchronous belt skeleton is made of carbon fiber cord.

[0008] Preferably, the lubricant is at least one of stearin, olein and trilinolein.

[0009] Preferably, the anti-scorch agent is anti-scorch agent CTP.

[0010] Preferably, the antioxidant is at least one of antioxidant NBC and antioxidant BLE.

[0011] Preferably, the vulcanizing agent is a mixture of dipentamethylenethiuram tetrasulfide, dithiuram 25, benzoyl peroxide and dicumyl peroxide in a mass ratio of 1:(0.5-1):0.6:(0.8-1.2).

[0012] Preferably, the coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.

[0013] Preferably, the inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:(0.8-1.2).

[0014] Preferably, the average diameter of the carbon fiber is 5-10 μm, and the aspect ratio is (15-25):1.

[0015] Preferably, the graphene oxide is a single-layer graphene oxide with a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm.

[0016] Preferably, the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosyn Technology Co., Ltd.

[0017] Preferably, the methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120.

[0018] Preferably, the epoxidized natural rubber is at least one of epoxidized natural rubber ENR25 and epoxidized natural rubber ENR50.

[0019] Preferably, the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with the grade of CSM3305, which is provided by Jilin Petrochemical.

[0020] Another object of the present invention is to provide a method for preparing the wear-resistant carbon fiber synchronous belt, comprising the following steps:

[0021] Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;

[0022] Step S2, corona discharge is performed on the synchronous belt skeleton, and then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for compression molding and vulcanization, and then cooled to room temperature to obtain a wear-resistant carbon fiber synchronous belt.

[0023] Preferably, the vulcanization in step S2 is specifically: vulcanization at a temperature of 145-155° C. and 8-12 MPa for 3-5 min, and then vulcanization at 160-170° C. and 10-15 MPa for 1-2 h.

[0024] Preferably, the number of corona discharges in step S2 is 10-20 times.

[0025] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0026] (1) The method for preparing the wear-resistant carbon fiber synchronous belt disclosed in the present invention has simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, low dependence on equipment, suitable for continuous large-scale production, and has high promotion and application value.

[0027] (2) The wear-resistant carbon fiber synchronous belt disclosed in the present invention comprises a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 35-45 parts of chlorosulfonated polyethylene, 15-20 parts of epoxidized natural rubber, 25-35 parts of methyl vinyl phenyl silicone rubber, 5-8 parts of cellulose nanocrystals, 10-20 parts of inorganic filler, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1-3 parts of 2,4,6-trivinyl 2-4 parts of boroxane, 3-5 parts of 2,6-diamino-9H-fluorene-9-one, 2-4 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 0.8-1.3 parts of 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 2-4 parts of coupling agent, 3-5 parts of vulcanizing agent, 1-3 parts of antioxidant, 0.4-0.6 parts of anti-scorch agent, 1-3 parts of lubricant; through the interaction between the raw materials, the synchronous belt has high strength, good wear resistance, excellent heat aging resistance and cold resistance. The blend of chlorosulfonated polyethylene, epoxidized natural rubber and methyl vinyl phenyl silicone rubber is used as the base material, combining their respective advantages, so that the above-mentioned properties of the product are better and the performance stability is better.

[0028] (3) The wear-resistant carbon fiber synchronous belt disclosed in the present invention introduces quinoxaline, fluorinated phenyl ether, fluorenone, cycloboroxane, azinone, chlorosulfonated polyethylene, natural rubber and methylphenyl silicone rubber into the molecular structure by rationally selecting the types and dosage ratios of the raw materials for preparing the synchronous belt film. These groups or structures, under the multiple effects of electronic effect, steric effect and conjugation effect, make the manufactured product have high strength, good wear resistance, excellent heat aging resistance and cold resistance.

[0029] (4) The wear-resistant carbon fiber synchronous belt disclosed in the present invention can improve the mechanical properties and the internal density of the material by adding cellulose nanocrystals and inorganic fillers; through the action of the vulcanizing agent, an interpenetrating network structure is formed, which can further improve the strength, wear resistance, heat aging resistance and cold resistance.

[0030] (5) The wear-resistant carbon fiber synchronous belt disclosed in the present invention can improve the compatibility between the film and the frame by corona discharge on the synchronous belt frame, thereby improving the performance stability of the manufactured synchronous belt and extending the service life of the product. DETAILED DESCRIPTION

[0031] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1

[0032] A wear-resistant carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 35 parts of chlorosulfonated polyethylene, 15 parts of epoxidized natural rubber, 25 parts of methyl vinyl phenyl silicone rubber, 5 parts of cellulose nanocrystals, 10 parts of inorganic filler, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-triazine 1 part of ketone, 2 parts of 2,4,6-trivinyl cycloboroxane, 3 parts of 2,6-diamino-9H-fluorene-9-one, 2 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 0.8 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 2 parts of coupling agent, 3 parts of vulcanizing agent, 1 part of antioxidant, 0.4 parts of anti-scorch agent and 1 part of lubricant; the synchronous belt skeleton is made of carbon fiber cord.

[0033] The lubricant is glyceryl stearate; the anti-scorching agent is anti-scorching agent CTP; the antioxidant is antioxidant NBC; the vulcanizing agent is a mixture of tetrapentamethylenethiuram sulfide, vulcanizing agent bis 25, benzoyl peroxide, and dicumyl peroxide in a mass ratio of 1:0.5:0.6:0.8; the coupling agent is silane coupling agent KH550; the inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:0.8; the average diameter of the carbon fiber is 5μm, and the aspect ratio is 15:1; The graphene oxide is a single-layer graphene oxide with a sheet diameter of 0.5 μm and a thickness of 0.8 nm; the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Naxun Technology Co., Ltd.; the methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120; the epoxidized natural rubber is epoxidized natural rubber ENR50; the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with a grade of CSM3305, and is provided by Jilin Petrochemical.

[0034] A method for preparing the wear-resistant carbon fiber synchronous belt comprises the following steps:

[0035] Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;

[0036] Step S2, corona discharge on the synchronous belt skeleton, then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for pressing and vulcanization, and after cooling to room temperature, a wear-resistant carbon fiber synchronous belt is obtained; the vulcanization is specifically: vulcanization at a temperature of 145°C and 8MPa for 3min, and then vulcanization at 160°C and 10MPa for 1h; the number of corona discharges is 10 times. Example 2

[0037] A wear-resistant carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 37 parts of chlorosulfonated polyethylene, 16 parts of epoxidized natural rubber, 27 parts of methyl vinyl phenyl silicone rubber, 6 parts of cellulose nanocrystals, 12 parts of inorganic filler, 1.5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2, 2.5 parts of 4,6-trivinyl cycloboroxine, 3.5 parts of 2,6-diamino-9H-fluorene-9-one, 2.5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 0.9 parts of 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 2.5 parts of coupling agent, 3.5 parts of vulcanizing agent, 1.5 parts of antioxidant, 0.45 parts of anti-scorch agent and 1.5 parts of lubricant; the synchronous belt skeleton is made of carbon fiber cord.

[0038] The lubricant is oleic acid glyceryl ester; the anti-scorching agent is anti-scorching agent CTP; the antioxidant is antioxidant BLE; the vulcanizing agent is a mixture of tetrapentamethylenethiuram tetrasulfide, vulcanizing agent bis 25, benzoyl peroxide, and dicumyl peroxide in a mass ratio of 1:0.6:0.6:0.9; the coupling agent is silane coupling agent KH560; the inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:0.9; the average diameter of the carbon fiber is 6 μm, and the aspect ratio is 17:1; The graphene oxide is a single-layer graphene oxide with a sheet diameter of 2 μm and a thickness of 0.9 nm; the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Naxun Technology Co., Ltd.; the methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120; the epoxidized natural rubber is epoxidized natural rubber ENR50; the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with a grade of CSM3305, and is provided by Jilin Petrochemical.

[0039] A method for preparing the wear-resistant carbon fiber synchronous belt comprises the following steps:

[0040] Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;

[0041] Step S2, corona discharge on the synchronous belt skeleton, then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for compression molding and vulcanization, and after cooling to room temperature, a wear-resistant carbon fiber synchronous belt is obtained; the vulcanization is specifically: vulcanization at a temperature of 147°C and 9MPa for 3.5min, and then vulcanization at 163°C and 11MPa for 1.2h; the number of corona discharges is 13 times. Example 3

[0042] A wear-resistant carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 40 parts of chlorosulfonated polyethylene, 18 parts of epoxidized natural rubber, 30 parts of methyl vinyl phenyl silicone rubber, 6.5 parts of cellulose nanocrystals, 15 parts of inorganic filler, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H) -trione 2 parts, 2,4,6-trivinyl cycloboroxane 3 parts, 2,6-diamino-9H-fluorene-9-one 4 parts, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane 3 parts, 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline 1 part, coupling agent 3 parts, vulcanizing agent 4 parts, antioxidant 2 parts, anti-scorch agent 0.5 parts, lubricant 2 parts; the synchronous belt skeleton is made of carbon fiber cord.

[0043] The lubricant is trilinoleyl glycerol; the anti-scorching agent is anti-scorching agent CTP; the antioxidant is antioxidant NBC; the vulcanizing agent is a mixture of tetrapentamethylenethiuram sulfide, vulcanizing agent bis 25, benzoyl peroxide, and dicumyl peroxide in a mass ratio of 1:0.8:0.6:1; the coupling agent is silane coupling agent KH570; the inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:1; the average diameter of the carbon fiber is 8μm, and the aspect ratio is 20:1; The graphene oxide is a single-layer graphene oxide with a sheet diameter of 3.5 μm and a thickness of 1 nm; the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Naxun Technology Co., Ltd.; the methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120; the epoxidized natural rubber is epoxidized natural rubber ENR50; the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with a grade of CSM3305, and is provided by Jilin Petrochemical.

[0044] A method for preparing the wear-resistant carbon fiber synchronous belt comprises the following steps:

[0045] Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;

[0046] Step S2, corona discharge on the synchronous belt skeleton, then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for pressing and vulcanization, and after cooling to room temperature, a wear-resistant carbon fiber synchronous belt is obtained; the vulcanization is specifically: vulcanization at a temperature of 150°C and 10MPa for 4min, and then vulcanization at 165°C and 13MPa for 1.5h; the number of corona discharges is 15 times. Example 4

[0047] A wear-resistant carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 43 parts of chlorosulfonated polyethylene, 19 parts of epoxidized natural rubber, 33 parts of methyl vinyl phenyl silicone rubber, 7.5 parts of cellulose nanocrystals, 19 parts of inorganic filler, 2.5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2 , 3.5 parts of 4,6-trivinyl cycloboroxane, 4.5 parts of 2,6-diamino-9H-fluorene-9-one, 3.5 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1.2 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 3.5 parts of coupling agent, 4.5 parts of vulcanizing agent, 2.5 parts of antioxidant, 0.55 parts of anti-scorch agent, and 2.5 parts of lubricant; the synchronous belt skeleton is made of carbon fiber rope.

[0048] The lubricant is a mixture of stearic acid glyceryl, oleic acid glyceryl, and trilinoleic acid glyceryl in a mass ratio of 1:2:3; the anti-scorching agent is anti-scorching agent CTP; the antioxidant is an antioxidant NBC and an antioxidant BLE mixed in a mass ratio of 3:5; the vulcanizing agent is a mixture of tetrasulfide dipentamethylenethiuram, vulcanizing agent bis 25, benzoyl peroxide, and dicumyl peroxide mixed in a mass ratio of 1:0.9:0.6:1.1. ; The coupling agent is a mixture of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570 in a mass ratio of 1:3:5; the inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:1.1; the average diameter of the carbon fiber is 9μm, and the aspect ratio is 23:1; the graphene oxide is a single-layer graphene oxide with a sheet diameter of 4.5μm and a thickness of 1.1nm; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.; the methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120; the epoxidized natural rubber is epoxidized natural rubber ENR50; the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with a grade of CSM3305, which is provided by Jilin Petrochemical.

[0049] A method for preparing the wear-resistant carbon fiber synchronous belt comprises the following steps:

[0050] Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;

[0051] Step S2, corona discharge on the synchronous belt skeleton, then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for pressing and vulcanization, and after cooling to room temperature, a wear-resistant carbon fiber synchronous belt is obtained; the vulcanization is specifically: vulcanization at a temperature of 153°C and 11MPa for 4.5min, and then vulcanization at 168°C and 14MPa for 1.8h; the number of corona discharges is 18 times. Example 5

[0052] A wear-resistant carbon fiber synchronous belt, comprising a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 45 parts of chlorosulfonated polyethylene, 20 parts of epoxidized natural rubber, 35 parts of methyl vinyl phenyl silicone rubber, 8 parts of cellulose nanocrystals, 20 parts of inorganic filler, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-triazine 3 parts of ketone, 4 parts of 2,4,6-trivinyl cycloboroxane, 5 parts of 2,6-diamino-9H-fluorene-9-one, 4 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1.3 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 4 parts of coupling agent, 5 parts of vulcanizing agent, 3 parts of antioxidant, 0.6 parts of anti-scorch agent and 3 parts of lubricant; the synchronous belt skeleton is made of carbon fiber cord.

[0053] The lubricant is glyceryl stearate; the anti-scorching agent is anti-scorching agent CTP; the antioxidant is antioxidant NBC; the vulcanizing agent is a mixture of tetrapentamethylenethiuram tetrasulfide, vulcanizing agent bis-25, benzoyl peroxide, and dicumyl peroxide in a mass ratio of 1:1:0.6:1.2; the coupling agent is silane coupling agent KH570; the inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:1.2; the average diameter of the carbon fiber is 10 μm, and the aspect ratio is 25:1; The graphene oxide is a single-layer graphene oxide with a sheet diameter of 5 μm and a thickness of 1.2 nm; the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Naxun Technology Co., Ltd.; the methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120; the epoxidized natural rubber is epoxidized natural rubber ENR50; the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with a grade of CSM3305, and is provided by Jilin Petrochemical.

[0054] A method for preparing the wear-resistant carbon fiber synchronous belt comprises the following steps:

[0055] Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film;

[0056] Step S2, corona discharge on the synchronous belt skeleton, then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for pressing and vulcanization, and after cooling to room temperature, a wear-resistant carbon fiber synchronous belt is obtained; the vulcanization is specifically: vulcanization at a temperature of 155°C and 12MPa for 5min, and then vulcanization at 170°C and 15MPa for 2h; the number of corona discharges is 20 times.

[0057] Comparative Example 1

[0058] A wear-resistant carbon fiber synchronous belt is substantially the same as that of Example 1, except that chlorosulfonated polyethylene is used instead of epoxidized natural rubber, and 2,6-diamino-9H-fluorene-9-one is not added.

[0059] Comparative Example 2

[0060] A wear-resistant carbon fiber synchronous belt is basically the same as Example 1, except that chlorosulfonated polyethylene is used instead of methyl vinyl phenyl silicone rubber, and 1,4-diacryl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline and cellulose nanocrystals are not added.

[0061] In order to further illustrate the beneficial technical effects of the wear-resistant carbon fiber synchronous belts involved in each embodiment of the present invention, relevant performance tests were carried out on the wear-resistant carbon fiber synchronous belts involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the tensile strength of the synchronous belt is determined according to GB / T 10716-2012; in order to control the variables, the ratio of the skeleton thickness to the thickness of the film in each test sample is 4:21; the carbon fiber cords are all made of M55J grade high-strength and high-modulus carbon fiber; the aging resistance is to place the synchronous belt rubber of each product in hot air at 125°C for artificial accelerated aging for 70 hours, cool it to room temperature, test and calculate the retention rate of the tensile strength of the synchronous belt rubber at room temperature, the larger the retention rate, the better the heat aging resistance, and the rubber tensile strength test refers to GB / T 528-2009, tensile rate 100mm / min; low temperature resistance is to place the synchronous belt rubber of each product at -40℃ for 5 hours, then restore it to room temperature, test and calculate the retention rate of the tensile strength of the synchronous belt rubber at room temperature, the larger the retention rate, the better the cold resistance performance, the rubber tensile strength test is carried out with reference to GB / T 528-2009, tensile rate 100mm / min; Akron abrasion is measured according to GB / T1689-1998. The tensile strength in Table 1 is the tensile strength of the synchronous belt, which is the test result rounded off according to the national standard requirements (the least significant digit is in the hundredth place).

[0062] As can be seen from Table 1, the wear-resistant carbon fiber synchronous belt disclosed in the embodiment of the present invention has better heat aging resistance, cold resistance and wear resistance than the comparative example product, and has greater strength. The addition of epoxidized natural rubber, methyl vinyl phenyl silicone rubber, 2,6-diamino-9H-fluorene-9-one, 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline and cellulose nanocrystals is beneficial to improving the above properties.

[0063] Table 1

[0064]

[0065] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A wear-resistant carbon fiber synchronous belt, characterized in that: The invention comprises a synchronous belt skeleton and a synchronous belt film wrapped around the synchronous belt skeleton, wherein the synchronous belt film is made of the following raw materials in parts by weight: 35-45 parts of chlorosulfonated polyethylene, 15-20 parts of epoxidized natural rubber, 25-35 parts of methyl vinyl phenyl silicone rubber, 5-8 parts of cellulose nanocrystals, 10-20 parts of inorganic filler, 1-3 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,4, 2-4 parts of 6-trivinyl cycloboroxine, 3-5 parts of 2,6-diamino-9H-fluorene-9-one, 2-4 parts of 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 0.8-1.3 parts of 1,4-diacryloyl-1,2,3,4-tetrahydro-6,7-dimethylquinoxaline, 2-4 parts of coupling agent, 3-5 parts of vulcanizing agent, 1-3 parts of antioxidant, 0.4-0.6 parts of anti-scorch agent and 1-3 parts of lubricant; the synchronous belt skeleton is made of carbon fiber cord.

2. The wear-resistant carbon fiber synchronous belt according to claim 1, characterized in that: The lubricant is at least one of stearin, olein and trilinolein; and the anti-scorching agent is anti-scorching agent CTP.

3. The wear-resistant carbon fiber synchronous belt according to claim 1, characterized in that: The antioxidant is at least one of antioxidant NBC and antioxidant BLE; the vulcanizing agent is a mixture of dipentamethylenethiuram tetrasulfide, vulcanizing agent bis-25, benzoyl peroxide, and dicumyl peroxide in a mass ratio of 1:(0.5-1):0.6:(0.8-1.2).

4. The wear-resistant carbon fiber synchronous belt according to claim 1, characterized in that: The coupling agent is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.

5. The wear-resistant carbon fiber synchronous belt according to claim 1, characterized in that: The inorganic filler is a mixture of carbon fiber and graphene oxide in a mass ratio of 1:(0.8-1.2); the average diameter of the carbon fiber in the inorganic filler is 5-10 μm, and the aspect ratio is (15-25):1; the graphene oxide is a single-layer graphene oxide with a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm.

6. The wear-resistant carbon fiber synchronous belt according to claim 1, characterized in that: The length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm.

7. The wear-resistant carbon fiber synchronous belt according to claim 1, characterized in that: The methyl vinyl phenyl silicone rubber is methyl vinyl phenyl silicone rubber IOTA-120; the epoxidized natural rubber is at least one of epoxidized natural rubber ENR25 and epoxidized natural rubber ENR50; the chlorosulfonated polyethylene is selected from chlorosulfonated polyethylene raw rubber with a grade of CSM3305.

8. A method for preparing the wear-resistant carbon fiber synchronous belt according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, putting chlorosulfonated polyethylene, epoxidized natural rubber, and methyl vinyl phenyl silicone rubber into an open mill for mixing, and alternately adding other raw materials, and mixing evenly to obtain a synchronous belt film; Step S2, corona discharge is performed on the synchronous belt skeleton, and then the synchronous belt film is attached to the synchronous belt skeleton, and then placed in a synchronous belt mold for compression molding and vulcanization, and then cooled to room temperature to obtain a wear-resistant carbon fiber synchronous belt.

9. The method for preparing the wear-resistant carbon fiber synchronous belt according to claim 8, characterized in that: The vulcanization in step S2 is specifically: vulcanization at a temperature of 145-155° C. and 8-12 MPa for 3-5 minutes, and then vulcanization at 160-170° C. and 10-15 MPa for 1-2 hours.

10. The method for preparing the wear-resistant carbon fiber synchronous belt according to claim 8, characterized in that: The number of corona discharges in step S2 is 10-20 times.

Citation Information

Patent Citations

  • A multifunctional carbon fiber reinforced polyurethane rubber synchronous toothed belt and preparation method thereof

    CN115679711B

  • Processing technology of rubber material for damping sleeve

    CN112500648A

  • Ceramic silicone rubber heat-shrinkable tubing, preparation method and application thereof

    CN115322575A